# Verify the relation between zeroes and coefficients of the quadratic polynomial ${x^2} - 4$.

Answer

Verified

365.1k+ views

Hint: For zeroes factorize and for coefficients compare with the standard form of quadratic equation and use sum and product of the roots formula to verify.

In the problem we are given a quadratic polynomial ${x^2} - 4$.

We have to find the relation between zeroes and coefficients of this expression.

Zeroes of the quadratic polynomial in variable $x$are the values of $x$for which the given

expression value equals zero. These values are also called the roots of that quadratic equation.

Given the expression in the problem, equating it to $0$gives the quadratic equation as

${x^2} - 4 = 0{\text{ (1)}}$

A general quadratic equation is of the form

$a{x^2} + bx + c = 0{\text{ (2)}}$

Where $a$ is the coefficient of ${x^2}$, $b$ is the coefficient of $x$and $c$ is the constant.

From the properties of quadratic equation in the form of equation $(2)$,it is known that,

Sum of roots $ = \dfrac{{ - 2b}}{a}{\text{ (3)}}$

Products of roots $ = \dfrac{c}{a}{\text{ (4)}}$

First, we need to find the roots of the quadratic equation $(1)$.

Factorising equation $(1)$ using identity ${a^2} - {b^2} = \left( {a + b} \right)\left( {a - b} \right)$, we

get,

$

{x^2} - {2^2} = 0 \\

\Rightarrow \left( {x - 2} \right)\left( {x + 2} \right) = 0 \\

\Rightarrow x = 2, - 2 \\

$

$ \Rightarrow x = 2$and$x = - 2$are the roots or zeros of the equation $(1)$

Now we need to convert equation $(1)$ into equation $(2)$form,

$

\Rightarrow \left( 1 \right){x^2} + \left( 0 \right)x - 4 = 0 \\

\Rightarrow a = 1,b = 0,c = - 4 \\

$

Using equations $(3)$and $(4)$ in above, we get,

Sum of roots $ = \dfrac{{ - 2b}}{a} = \dfrac{{ - 2 \times 0}}{1} = 0$

Products of roots $ = \dfrac{{ - 4}}{1} = - 4$

Also, since $x = 2$and$x = - 2$are the roots or zeros of the equation $(1)$,we get

Sum of roots $ = - 2 + 2 = 0$

Products of roots $ = - 2 \times 2 = - 4$

Since the results obtained above are in consensus with the previous results,

Hence relation $(3)$and $(4)$are verified, that is, relation between zeroes and coefficients of the

quadratic polynomial ${x^2} - 4$ are verified.

Note: Always try to remember the formula for sum of roots and product of roots for quadratic polynomials. Also, the polynomial should always be converted into general form as explained above before using the formulas.

In the problem we are given a quadratic polynomial ${x^2} - 4$.

We have to find the relation between zeroes and coefficients of this expression.

Zeroes of the quadratic polynomial in variable $x$are the values of $x$for which the given

expression value equals zero. These values are also called the roots of that quadratic equation.

Given the expression in the problem, equating it to $0$gives the quadratic equation as

${x^2} - 4 = 0{\text{ (1)}}$

A general quadratic equation is of the form

$a{x^2} + bx + c = 0{\text{ (2)}}$

Where $a$ is the coefficient of ${x^2}$, $b$ is the coefficient of $x$and $c$ is the constant.

From the properties of quadratic equation in the form of equation $(2)$,it is known that,

Sum of roots $ = \dfrac{{ - 2b}}{a}{\text{ (3)}}$

Products of roots $ = \dfrac{c}{a}{\text{ (4)}}$

First, we need to find the roots of the quadratic equation $(1)$.

Factorising equation $(1)$ using identity ${a^2} - {b^2} = \left( {a + b} \right)\left( {a - b} \right)$, we

get,

$

{x^2} - {2^2} = 0 \\

\Rightarrow \left( {x - 2} \right)\left( {x + 2} \right) = 0 \\

\Rightarrow x = 2, - 2 \\

$

$ \Rightarrow x = 2$and$x = - 2$are the roots or zeros of the equation $(1)$

Now we need to convert equation $(1)$ into equation $(2)$form,

$

\Rightarrow \left( 1 \right){x^2} + \left( 0 \right)x - 4 = 0 \\

\Rightarrow a = 1,b = 0,c = - 4 \\

$

Using equations $(3)$and $(4)$ in above, we get,

Sum of roots $ = \dfrac{{ - 2b}}{a} = \dfrac{{ - 2 \times 0}}{1} = 0$

Products of roots $ = \dfrac{{ - 4}}{1} = - 4$

Also, since $x = 2$and$x = - 2$are the roots or zeros of the equation $(1)$,we get

Sum of roots $ = - 2 + 2 = 0$

Products of roots $ = - 2 \times 2 = - 4$

Since the results obtained above are in consensus with the previous results,

Hence relation $(3)$and $(4)$are verified, that is, relation between zeroes and coefficients of the

quadratic polynomial ${x^2} - 4$ are verified.

Note: Always try to remember the formula for sum of roots and product of roots for quadratic polynomials. Also, the polynomial should always be converted into general form as explained above before using the formulas.

Last updated date: 28th Sep 2023

â€¢

Total views: 365.1k

â€¢

Views today: 7.65k

Recently Updated Pages

What do you mean by public facilities

Please Write an Essay on Disaster Management

Paragraph on Friendship

Slogan on Noise Pollution

Disadvantages of Advertising

Prepare a Pocket Guide on First Aid for your School

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

What is meant by shramdaan AVoluntary contribution class 11 social science CBSE

The equation xxx + 2 is satisfied when x is equal to class 10 maths CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

An alternating current can be produced by A a transformer class 12 physics CBSE

What is the value of 01+23+45+67++1617+1819+20 class 11 maths CBSE

Give 10 examples for herbs , shrubs , climbers , creepers